'SPEAK AGAIN': LIFE, LOVE AND LANGUAGE IN KING LEAR. Issue 2 (April 2017) - Montemaggi, Vittorio
Abstract : In a version of his spoken address, Vittorio Montemaggi demonstrates how King Lear invites us to reflect on theatre and the nature of Resurrection as the 'theological horizon' in which language and love are spoken.